E-Governance: The Implication of Next Social Generation Welfare Information System - Mulyana Abdul Aziz, Yaya; Ariesmansyah, Andre (UI Scholars Hub, 2023)
Accelerating bureaucracy can be performed by e-governance present in order to improve the quality of government administration in the world. E-governance draft is closely related to the development of information and communication technology (ICT) globally. One form of embodiment of e-governance is the implementation of a smart city. smart cities are expected to be able to become a liaison between the demands of the community in appropriate, effective, and efficient services from the city government, by utilizing ICT. There are various related definitions of smart city in this world. One of them is as explained by Nam and Pardo who state